Migraine and Epilepsy in Children: A Narrative Review of Comorbidity and Similar Treatment Option - Momen, Ali Akbar; Jelodar, Gholamreza; azizi malamiri, reza (Iranian Journal of Child Neurology, 2024)
Migraine and epilepsy belong to the category of chronic paroxysmal neurological disorders and share numerous clinical features, as well as potential treatment options. This narrative review emphasizes the similarities between pediatric migraine and epilepsy, exploring epidemiology, pathophysiology, genetics, clinical presentation, and pharmacology. Although various syndromes exhibit symptoms common to both conditions, further research is needed to clarify the underlying pathophysiological and genetic connections contributing to their coexistence. Prophylactic medications used in the management of both migraines and epilepsy exhibit similar pharmacological characteristics. The review assesses treatment strategies for epilepsy and migraines, emphasizing antiseizure medications alongside nonpharmacological interventions like ketogenic diet, supplements, and vagal nerve stimulation. It aims to highlight how these interventions, originally targeted for epilepsy, may also show promise in preventing migraines. The urgent need for further randomized, controlled clinical trials investigating both pharmacological and nonpharmacological interventions for treating both disorders is emphasized, aiming to pave the way for innovative therapeutic strategies.